The next challenge: from mixed to merged methods. Issue 4 (7th December 2015) - Gobo, Giampietro
Abstract : Purpose: – In social sciences, after having witnessed several "turns" (cognitive, linguistic, pragmatic, interactional), the authors observe the rise of the "qualitative turn". Therefore quantitative research methods are not mainstream anymore. One effect of this rebalance between quality and quantity is the recent "resurgence" of mixed methods. However, a new challenge presses social research: creating new methods, which could combine both qualitative and quantitative approaches in a single instrument, squeezing the advantages of both in a single technique. With the benefit of lowering the costs and making more consistent the findings. Some "merged" methods already exist and QROM could be a visionary laboratory. The paper aims to discuss these issues. Design/methodology/approach: – An overview of recent research on the spread and use of social research methods in different countries. Findings: – In social sciences quantitative methods are not mainstream anymore. Research limitations/implications: – The time has come for a further step in the direction of a full integration of qualitative and quantitative methods. Practical implications: – Envisioning the future needs for creating new methods, which could combine both qualitative and quantitative approaches in a single instrument, squeezing the advantages of both in a single technique. With the benefit of lowering the costs and making more consistent the research findings. Some "merged" methods already exist and QROM could be a visionary laboratory. Social implications: – The rise of "qualitative turn" in social sciences will change the power relations in academy and in the market research. New generations of researchers will bring social research back to the times of Chicago School, where qualitative research was dominated. Only posterity will know if this will be good or not. Originality/value: – This brief paper envisions the need to go beyond the current "mixed" methods fashion in favour of full "merged" methods research.